Development of prototype instructional materials in biology for visually impaired high school students - Cabales, Elizabeth M. 1939- (1986)
The prototype instructional materials designed to provide the visually impaired high school students first-hand experiences in the study of biological structures perceivable through the tactile and auditory senses is the focus of the paper. The instructional materials have been prepared so that the visually impaired learner will be provided with adequate instruction and meaningful participation in both indoor and outdoor activities in biology by utilizing their remaining senses to the fullest.
Thesis (M.Ed.)--University of the Philippines, Diliman.
Vita.
Keywords: Physically handicapped children -- Education; Biology -- Study and teaching (Secondary).